Dampak Aktifitas Fisik dengan Kejadian Obesitas pada Remaja di Kotamobagu - Moh. Rizki Fauzan; Sarman Sarman (Universitas Gorontalo, 2022)
Obesity is a global public health problem and contributes to 2.6 million deaths worldwide each year. The prevalence of obesity has increased in various countries, including in Southeast Asia and South Asia. One of the causes of the high prevalence of obesity in adolescents is physical activity. This study aims to examine the effect of physical activity on incidence of obesity adolescents in Kotamobagu area of North Sulawesi. This type of research uses a case control study method which was carried out in public and private high schools in Kotamobagu from May to July 2022. The population is all teenagers from public and private high schools in Kotamobagu had active status many as 10,314 person. The research sample was 298 people who divided 2 groups of 149 cases and 149 controls and a total sample 298 people determined by Lemeshow formula. The results bivariate analysis using chi square test showed that in the group of adolescents with no obesity, the majority of class 1 SMA and 2 SMA were 62 people (41,6%) and 80 women (53,7%). Meanwhile, in the group of adolescents with obesity, the majority of class 1 SMA were 70 people (47%) and female were 99 people (66,4%). The results of the bivariate test showed that there was a significant effect between adolescent physical activity p value (0,000) on incidence of obesity in adolescents in Kotamobagu area. It is hoped that the central government of Kotamobagu should recommend starting frequent physical activity to be able to lose weight and also always pay attention to a healthy daily diet.